EFEK GANDA DAN PERMINTAAN KONSUMEN OBJEK WISATA DANAU WISATA SEJARAH SEBEDANG DI DESA SEMPALAI KECAMATAN SEBAWI KABUPATEN SAMBAS - Aris, Ahmad; Hardiansyah, Gusti; Erianto, Erianto (Universitas Tanjungpura, 2019)
Danau Wisata Sejarah Sebedang (DWSS) is one of the tourist attractions located in Sambas district. Most of the economic impacts that exist on these attractions are not widely known. Therefore, there is a need for research to determine the economic value and factors that influence tourism demand for this tourist attraction. The purpose of this research is to analyze the economic impact felt by the surrounding community. To achieve the research objectives used the Travel Cost Method and the Keynesian multiplier. The object of research is visitors who come to DWSS, business units and local workforce. Visitors of Sebedang Lake tourism objects are generally dominated by community groups aged 25 years - 35 years, with high school education level and equivalent, their income level is more than Rp. 2,000,000.00 per month. The factors that influence recreational demand to DWSS are travel costs and travel time. The average tourist expenditure is Rp. 56,295.00 with 3,253 monthly visits. The existence of this DWSS object has an economic impact on the local community around, such as the direct economic impact in the form of business unit owner's income, which is 66%. While the indirect impact in the form of labor income is 1%. Then the further impact is in the form of labor expenditure of 59% which is used for food needs. The Keynesian lncome Multiplier value is 2.64, Type 1 Ratio Income Multiplier is 1.19 and Type 2 Ratio Income Multiplier is 1.21.Keywords : Sebedang Lake,economic impact, Natural Recreation